Orthodontic-surgical treatment of a patient with Marfan Syndrome and Obstructive Sleep Apnea Syndrome: a case report with a 9-year follow-up - Rodrigues, Willian Caetano [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Oliveira, Marina Reis [UNESP]; Piveta, Ana Cláudia Gabrielli [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP] (Faculdade São Leopoldo Mandic, 2019)
Marfan’s (MFS) syndrome is characterized by a defect in the connective tissue, which affects multiple organic systems. Therefore, the management of these patients requires a multidisciplinary approach. This case reports the orthodontic-surgical treatment of a patient who presented both Marfan’s and obstructive sleep apnea syndrome. Patient had malocclusion, TMJ clicking, vertical maxillary excess, mandibular retrognathia, severe esthetic compromise, signs and symptoms of obstructive sleep apnea syndrome, as well as alterationsin joints, cardiovascular and respiratory systems. He was treated with bimaxillary surgery aimed to enhance esthetics, occlusion and address the obstructive sleep apnea syndrome. The clinical results show that a desirable functional occlusion was achieved and both patient’s facial esthetics and quality of life were significantly improved. After a 9-year follow-up period, these pleasing features were maintained. The diagnosis and management of Marfan’s patients is challenging and require multidisciplinary follow-up.

A síndrome de Marfan (SMF) é caracterizada por um defeito no tecido conjuntivo que afeta múltiplos sistemas orgânicos. Portanto, o manejo desses pacientes requer uma abordagem multidisciplinar. Este artigo relata o tratamento ortodôntico-cirúrgico de um paciente com síndrome de Marfan e síndrome da apneia obstrutiva do sono (SAOS). Ele manifestava má oclusão, estalidos na ATM, excessovertical de maxila, retrognatismo mandibular, comprometimento estético severo, sinais e sintomas de síndrome da apneia obstrutiva do sono, além de alterações nas articulações, nos sistemas cardiovascular e respiratório. O tratamento incluiu cirurgia bimaxilar com o objetivo de melhorar a estética, a oclusão e tratar sua apneia obstrutiva do sono. Os resultados clínicos mostram que uma oclusãofuncional desejável foi alcançada e tanto a estética facial quanto a qualidade de vida do paciente foram significativamente melhoradas. Após um período de 9 anos de acompanhamento, essas características agradáveis foram mantidas. O diagnóstico e tratamento de pacientes com síndrome de Marfan é desafiador e requer acompanhamento multidisciplinar.
Tratamento ortodôntico-cirúrgico de um paciente com Síndrome de Marfan e Síndrome da Apnéia Obstrutiva do Sono: relato de caso com 9 anos de acompanhamento
Keywords: Marfan’s syndrome; Obstructive sleep apnea syndrome; Orthognathic surgery; Síndrome de Marfan; Síndrome da apneia obstrutiva do sono; Cirurgia ortognática